The political economy of psychology: Parker, I & Spears, R (eds) (1996) Psychology and society: Radical theory and practice. London: Pluto Press. ISBN 0-7453-0879-1 pbk. 248 pages. - Terre Blanche, Martin (PINS-Psychology in Society, 2026)
That Marxism has lost something of its lustre as an academic brand name is illustrated once again by this collection of articles on psychology and society, the original title of which, Psychology and Marxism, had to be withdrawn for marketing reasons. The trouble, as Hayes reminds us in his chapter on "The psychology of everyday life", is that even though Marxism proved itself to have considerable explanatory capacity as a theory of the capitalist west, it offered few tools for critiquing the various forms of crude totalitarianism which were perpetrated in its name, and was therefore discredited along with the regimes which claimed to draw inspiration from its tenets. Ironically, however, the collapse of communism could now breathe new life into Marxist theory, relieved of the burden of having to defend the indefensible, and thus able to focus more clearly on its continuing critique of the capitalist world order. Psychology and society may be one of the early indications of such a Marxist renaissance.